SISTEM INFORMASI PRESENSI DAN PENGGAJIAN GURU DENGAN RADIO FREQUENCY IDENTIFICATION (RFID) MENGGUNAKAN E-KTP: Studi Kasus: SD Negeri 1 Permanu, Kabupaten Malang - Choirina, Priska; Darajat, Pangestuti Prima; Yuliono, Gun (Universitas Methodist Indonesia, 2023)
In the current technological era, several educational institutions' teacher attendance and payroll system uses manual recording in a book for each attendance and payroll. This research aims to design and build a teacher attendance and payroll system integrated with a database using radio frequency identification (RFID). This attendance and payroll system consists of several main components, namely E-KTP used as a substitute for ID cards and RFID readers used to read teacher attendance information. The attendance and payroll system has several features, namely, attendance and return scan page, attendance summary report and payroll report in form of salary report. The method used in this design is the Rapid Application Development (RAD) method. The method provides much faster development and better results than the traditional cycle. The information system testing used is blackbox and whitebox testing. The results of implementing the Attendance & Remuneration Information System in SD Negeri 1 Permanu have shown that the system improves the attendance of teachers.